Predictive capacity of anthropometric indicators for abdominal fat in the oldest old - Vanessa Ribeiro Santos; Diego Giulliano Destro Christofaro; Igor Conterato Gomes; Lionai Lima dos Santos; Ismael Forte Freitas Júnior (Universidade Federal de Santa Catarina, 2013)
Cardiovascular diseases are a growing public health problem that affects most people over the age of 65 years and abdominal obesity is one of the risk factors for the development of these diseases. There are several methods that can be used to measure body fat, but their accuracy needs to be evaluated, especially in specific populations such as the elderly. The aim of this study was to assess the accuracy of anthropometric indicators to estimate the percentage of abdominal fat in subjects aged 80 years or older. A total of 125 subjects ranging in age from 80 to 95 years (83.5 ± 3), including 79 women (82.4 ± 3years) and 46 men (83.6 ± 3 years), were studied. The following anthropometric indicators were used: body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR), and waist-to-height ratio (WHtR). The percentage of abdominal fat was measured by DEXA. Sensitivity and specificity were analyzed using an ROC curve. The sensitivity, specificity and AUC were 0. 578, 0. 934 and 0. 756 for BMI, respectively; 0.703, 0.820 and 0.761 for WC; 0.938, 0.213 and 0.575 for WHR, and 0.984, 0.344 and 0.664 for WHtR. BMI and WC were the anthropometric indicators with the largest area under the curve and were therefore more adequate to identify the presence or absence of abdominal obesity.